Vision Impairment and Associated Factors in a Coastal Province of Southern China: The Fujian Eye Study - Li, Yang; Hu, Qinrui; Li, Xiaoxin; Hu, Yonghua; Qin, Xueying; Wang, Bin; Ren, Tao (Frontiers in Photonics, 2022)
Purpose: To evaluate the prevalence and correlations of vision impairment (VI) among urban and rural adults in a coastal province of Southern China. Design: Population-based cross-sectional study. Methods: The study was designed to recruit residents aged over 50 years in randomly sampled communities of Fujian Province from 2018 to 2019. Participants completed a questionnaire about socioeconomic and biological factors and underwent visual examinations. Best corrected visual acuity (BCVA) was measured for the participants to assess VI, which was defined as best corrected visual acuity (BCVA) in better eyes of 20/60 or worse. Results: A total of 6,823 participants were included in this report. VI prevalence was higher in inland populations, compared with that in coastal populations (5.08 vs. 2.79%, p < 0.001), but there was no significant difference between urban populations and rural populations (2.97 vs. 3.73%, p = 0.082). VI was significantly associated with sociodemographic and biological factors, which included age, educational background, income, and refractive error. Sex and urbanization were not statistically significantly associated with VI. Conclusion: High prevalence of VI in southeast China suggested need for more accessible services and favorable policies for enhancing eye health in rural and inland elderly people.